2015
DOI: 10.4238/2015.december.9.19
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity analysis of Capparis spinosa L. populations by using ISSR markers

et al.

Abstract: ABSTRACT. Capparis spinosa L. is an important medicinal species in the Xinjiang Province of China. Ten natural populations of C. spinosa from 3 locations in North, Central, and South Xinjiang were studied using morphological trait inter simple sequence repeat (ISSR) molecular markers to assess the genetic diversity and population structure. In this study, the 10 ISSR primers produced 313 amplified DNA fragments, with 52% of fragments being polymorphic. Unweighted pair-group method with arithmetic average (UPGM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Subcluster 1 of Cluster I has only The three clusters resolved by STRUCTURE are consistent with those inferred in the dendrogram. Using the same type of molecular marker, Liu et al (2015) observed similar results, the formation of three groups in C. spinosa. Accession VCUR-802 from Itabaiana/ SE shows some affinity to each of the three groups in the STRUCTURE plot, suggesting admixture.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Subcluster 1 of Cluster I has only The three clusters resolved by STRUCTURE are consistent with those inferred in the dendrogram. Using the same type of molecular marker, Liu et al (2015) observed similar results, the formation of three groups in C. spinosa. Accession VCUR-802 from Itabaiana/ SE shows some affinity to each of the three groups in the STRUCTURE plot, suggesting admixture.…”
Section: Discussionsupporting
confidence: 66%
“…Because they are dominant loci, it is not possible to distinguish heterozygotes from homozygotes; however, multiple loci can be produced from each amplification with polymerase chain reaction (PCR; Goulão and Oliveira, 2001). Several genetic diversity studies on medicinal plants, both in natural populations and in collections of germplasm banks, have been carried out using ISSRs, such as studies on Capparis spinosa, Eucommia ulmoides, and Pogostemon cablin (Liu et al, 2015;Yu et al, 2015;Sandes et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…(Brito et al, 2016), in Capparis spinosa L. (Liu et al, 2015), in Rheum (Tabin et al, 2016), in Withania somnifera (Khan and Shah, 2016), and in Panax stipuleanatus Tsai (Trieu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Using random-amplified polymorphic DNA (RAPD) and isoenzyme approaches, Wang et al (2008) reported the low diversity of T. sinensis natural resources in China. Compared with RAPD, ISSR and SRAP have higher reproducibility and are more effective for genetic diversity analyses and germplasm evaluation (Shao et al, 2010;Medri et al, 2011;Niu et al, 2015;Liu et al, 2008Liu et al, , 2015Souza-Sobreira et al, 2015). Using these two marker systems, we studied the genetic diversity and genetic relationships of five T. sinensis populations (100 individuals/sample) representing different climates and geographical locations in China.…”
Section: Introductionmentioning
confidence: 99%